CDK4/6 inhibitors in the treatment of metastatic breast cancer. Choosing optimal therapy for estrogen-receptor-positive HER2-negative metastatic breast cancer: analysis of doctors’ preferences (“Prometheus”) in Russia – first results of the survey - E. V. Artamonova (Opuholi Ženskoj Reproduktivnoj Sistemy, 2021)
The emergence of a new class of drugs – inhibitors of cyclin-dependent kinases 4/6 (CDK4/6) – has changed the paradigm of treatment of patients with luminal HER2 negative metastatic breast cancer. Their effectiveness is confirmed not only by randomized, but also observational studies on a wide heterogeneous population of patients from daily clinical practice; the use of these drugs in the 1st line is significantly expanding in the world. On the territory of the Russian Federation, an observational study of Prometheus was carried out, the purpose of which was to assess the frequency of prescribing CDK4/6 inhibitors, as well as other types of treatment in 1–2nd lines in real clinical practice in Russia, as well as factors and preferences of doctors influencing the choice of therapy. A survey of the target audience, whose answers can be considered reliable and reflecting today’s Russian clinical practice in the treatment of breast cancer, showed that, despite the fact that the overwhelming majority of doctors (78 %) believe that the maximum benefit from the appointment of CDK4/6 inhibitors is expected for the 1st line therapy, in real clinical practice, only 35 % of doctors practice 1 st line prescription. In the 2nd line of therapy, CDK4/6 inhibitors are prescribed by 45 % of experts, in the 3rd (or more) line – 20 %. According to the respondents, the main obstacle to the appointment of CDK4/6 inhibitors is the unresolved issues of the availability of therapy (44 %) and its cost (34 %). Among all the proposed clinical criteria, only the criterion “visceral metastases with impaired function of internal organs” influences the decision not to prescribe a combination of hormonal therapy and a CDK4/6 inhibitor in 1–2nd lines of therapy. Criteria such as ECOG status, menopause status, tumor subtype preceding chemotherapy, timing of progression do not determine the choice when deciding not to prescribe combination therapy.